(untitled) (London Journal of Engineering Research, 2024)
In this work, road petroleum bitumen was modified with styrene butadiene rubber, butyl rubber and nano-sized dolomite. As a result of the modification, the basic physical, mechanical and chemical characteristics of the resulting composition were improved. It has been shown that the penetration, softening temperature and adhesive properties of bitumen as a result of modification with polymers are improved by 1.3 times compared to standard unmodified bitumen. The use of rubbers such as butyl rubber, styrene butadiene rubber and dolomite improves the mechanical strength and adhesive properties of road bitumen. Thus, the resulting polymer bitumen is an excellent binding system for the resulting asphalt-bitumen mixture.